The Economic Effects of Fiscal Consolidation with Debt Feedback - Estevao, Marcello (IMF Working Papers; Working Paper ;, 2013)
The past several years of recession and slow recovery have raised much interest on the effect of fiscal stimulus on economic activity, even as high public debts in many countries would call for fiscal consolidation. To evaluate the delicate balance between stimulus and consolidation requires measuring the size of fiscal multipliers, which often depends on having quarterly data so that exogenous fiscal policy shocks can be identified. We estimate fiscal multipliers using a novel methodology for identifying fiscal shocks within a structural vector autoregressive approach using annual data while controling for debt feedback effects. The estimation focuses on regions with scarce quarterly data (mostly low-income countries), and uses results for advanced economies, emerging market countries, and other broad groupings for which alternative estimates are available to validate the methodology. Differently from advanced and emerging market economies, fiscal consolidation in low-income countries has only a small temporary negative effect on growth while raising medium-term output. Shifting the composition of public spending toward capital expenditure further supports long-run growth.